Correlation and discordance of anti-mullerian hormone with follicle stimulating hormone in infertile women with premature ovarian insufficiency and diminished ovarian reserve - Ishrat, Shakeela; Deeba, Farzana; Anwary, Shaheen Ara; Banu, Jesmine (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The objective of the study was to explore the correlation and discordance of anti-mullerian hormone (AMH) and follicle stimulating hormone (FSH) in the selected population of premature ovarian insuffiency and diminished ovarian reserve. Methods: This was a retrospective analysis of the data obtained from the women who presented to the Gynae Endocrine Clinic of the Infertility unit of the Department of Obstetrics & Gynaecology from 2015 to 2017. Discordance was defined as abnormal basal FSH (>10 IU/l) with assuring AMH (>1 ng/ml). Statistical analysis was done with SPSS version 23. Results: There were 36 women with premature ovarian insufficiency and 35 women with diminished ovarian reserve. The correlations between basal FSH and AMH are not significant. AMH values are relatively higher in younger age groups. There are extreme high outliers in both POI and DOR groups, more in younger age group. The discordance between AMH and basal FSH was more in women categorized to have diminished ovarian reserve, compared to women with premature ovarian insufficiency. Conclusions: Those women who are younger than 35 years and have high FSH combined with reassuring AMH should be counseled with care regarding the prognosis of their treatment.